Adult hydrocephalus - Rigamonti, Daniele, 1951-; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
Adult hydrocephalus is an insidious yet treatable condition that develops slowly, with usual onset around 60 years of age. It is poorly recognized and many cases are not diagnosed until late in the course of disease, leading to poorer patient outcomes and a high financial cost to healthcare providers. The resulting neurological symptoms include gait/balance problems, loss of bladder control, and a cognitive decline leading to dementia, which is often mistaken for Alzheimer's disease. This book - the first published on this topic since 1993 - provides comprehensive guidelines to improve the speed and accuracy of diagnosis, and covers various neurosurgical techniques used to treat the disease, including the insertion of different types of shunts and endoscopic third ventriculostomy. This is essential reading for neurologists, neurosurgeons, family physicians, and radiologists who may well encounter adult patients with hydrocephalus more often than they realize.
Anatomy and physiology of the cerebrospinal fluid system -- Neuropathology of human hydrocephalus -- Animal models of hydrocephalus -- Genetics of hydrocephalus -- The Epidemiology of hydrocephalus -- Pathophysiology of gait dysfunction in normal pressure hydrocephalus -- The Pathophysiologic basis of cognitive dysfunction in idiopathic normal pressure hydrocephalus -- Incontinence and lower urinary tract symptoms in normal pressure hydrocephalus -- Normal pressure hydrocephalus grading scales -- The Differential diagnosis of normal pressure hydrocephalus -- Core imaging in adult hydrocephalus -- Imaging of the cerebrospinal fluid circulation -- Cerebrospinal fluid dynamics and infusion techniques -- Monitoring of intracranial pressure and assessment of cerebrospinal fluid dynamics -- Cerebrospinal fluid biomarkers in ikiopathic normal pressure hydrocephalus -- Hydrocephalus shunt procedures -- Hydrocephalus shunts: principles, hardware, shunt testing -- Management of shunts in normal pressure hydrocephalus: follow-up and late complications -- Endoscopic third ventriculostomy: indications, technique, outcome, and complications -- Outcome of idiopathic normal pressure hydrocephalus -- Normal pressure hydrocephalus syndrome secondary to hemorrhage, infection, and malignancy -- Low-pressure syndromes and cerebrospinal fluid leaks: diagnosis and management -- Management of the adult with congenital hydrocephalus -- Management of hydrocephalus with associated cerebrospinal fluid pathologies -- Chiari malformation and hydrocephalus in adults -- Pseudotumor cerebri syndrome.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Hydrocephalus -- Treatment; Hydrocephalus -- Etiology; Cerebrospinal fluid pressure; Electronic books